Enhancing Customer Value through Digital Marketing Channels - Azzahra, Shalsabila; Hasan Ridwan, Ahmad (Journal of Economicate Studies, 2022)
Digital technology is reshaping marketing by transforming how businesses engage with customers and deliver value. This study explores how digital platforms—such as CRM systems, AI tools, mobile applications, and social media—enhance customer engagement and satisfaction. Drawing on theories like Service-Dominant Logic and Omnichannel Marketing, it provides a conceptual analysis of digital value creation. Using qualitative methods and data from scholarly publications, the research identifies personalization, responsiveness, and seamless multichannel integration as key drivers of value. Findings suggest that firms must align digital strategies with evolving customer expectations through agile structures and cultural sensitivity. The study contributes theoretically by integrating global and local perspectives, and offers practical implications for businesses seeking to innovate through digital transformation. It concludes that strategic digital integration is essential for sustained competitiveness and long-term customer loyalty in dynamic environments.